E-tivities : the key to active online learning - Salmon, Gilly (Routledge, 2013)
The world of learning and teaching is at a watershed; confronted by challenges to previous educational models. One learning future lies in impactful, purposeful, active online activities, or 'e-tivities', that keep learners engaged, motivated, and participating. Grounded in the author's action research, E-tivities, 2nd Edition assuredly illustrates how technologies shape and enhance learning and teaching journeys. In this highly practical book, Gilly Salmon maintains her exceptional reputation, delivering another powerful guide for academics, teaching professionals, traine.